2003
DOI: 10.1097/00001622-200305000-00002
|View full text |Cite
|
Sign up to set email alerts
|

The role of gamma knife radiosurgery in the treatment of primary and metastatic brain tumors

Abstract: With the widespread diffusion of stereotactic radiosurgical procedures, GKR treatments have gained considerable momentum as a major therapeutic option for patients harboring primary or metastatic brain tumors. Present results in high grade gliomas indicate a potential palliative role of this technique. The overall low radiosensitivity of these oncotypes and their infiltrative nature-with the resulting problems in properly defining the tumor target-are still a major obstacle to further development of the approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 93 publications
0
12
0
Order By: Relevance
“…Although recent technologies such as intensity-modulated radiation therapy (IMRT) and gamma knife (stereotactic radiosurgery), which precisely aim to target tumor, greatly reduced the damage to normal tissues, delivery of high-dose ionizing radiation (IR) is still limited due to the damage to surrounding normal tissues (Purdy, 2002;Gerosa et al, 2003). One possible solution for this problem is to preferentially sensitize tumor cells to IR, which could reduce the dose of IR in treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Although recent technologies such as intensity-modulated radiation therapy (IMRT) and gamma knife (stereotactic radiosurgery), which precisely aim to target tumor, greatly reduced the damage to normal tissues, delivery of high-dose ionizing radiation (IR) is still limited due to the damage to surrounding normal tissues (Purdy, 2002;Gerosa et al, 2003). One possible solution for this problem is to preferentially sensitize tumor cells to IR, which could reduce the dose of IR in treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary results for HGA suggest that SRS increases local tumor control rate, progression free and overall survival, and quality of life (Blomquist et al, 2005;Gerosa et al, 2003). It's shown that the SRS delays neurological deterioration in HGA and provides better KPS during the course of the disease (Jagannathan et al, 2004).…”
Section: Tumor Control and Functional Outcomementioning
confidence: 99%
“…[33][34][35] Finally, SRS is preferred in surgically inaccessible sites, such as deep-seated tumors or brainstem tumors. 7,8 Although the toxicity profile is favorable, SRS can only be considered preferable to surgery if tumor control is equivalent or better. No randomized trials have compared SRS with surgery, and therefore it is unknown whether one method provides superior control compared with the other.…”
Section: Addition Of Srs To Wbrt In Patients With Single Brain Metastmentioning
confidence: 99%
“…Brain metastases affect 20 to 40% of cancer patients, [2][3][4][5] and the incidence may be increasing due to improvements in imaging, allowing earlier detection, 6 and improvements in the systemic treatment of cancer, allowing patients to live longer with extracranial disease. 7,8 Approximately one quarter of patients with brain metastases die of a neurologic cause, 9 and brain metastases result in symptoms in more than two thirds of patients. 2,10 Due to the morbidity and mortality related to brain metastases, their optimal treatment with currently available therapies as well as the investigation of novel therapies is being actively pursued by oncologists.…”
mentioning
confidence: 99%